Curriculum Development and Learning Innovation to Improve Teacher Professionalism - Munawir; Firdausy Nuzula; Mila Nailis Salamah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article discusses curriculum development and learning innovation as an effort to improve teacher professionalism. In the context of ever-evolving education, teacher professionalism is the main key to improving the quality of learning and producing quality graduates. Curriculum development based on the need for 21st century competence, as well as the implementation of creative and relevant learning innovations, is expected to enrich students' learning experience and strengthen teachers' pedagogical skills. This article also examines various curriculum models that can be applied, including competency-based curriculum and integrative curriculum, as well as various innovative learning methods such as project-based learning, technology utilization, and active learning.